Réponses

2014-01-19T17:12:51+01:00
A= 5x + 3 = 8x + 17 
A= 5x - 8x = 17 + 3
A= -3x = 20
A= -3x/3 = 20/3
-x = 20/3
x= -20/3

B= -3x -13 = 8x - 5
B= -3x - 8x = -5 +13
B= - 11x = 8
B= -11x/11 = 8/11
-x = 8/11
x = -8/11

C= 5x -5 = 17x - 11
C= 5x - 17x = -11 + 5
C= -12x = - 6
C= -12x/12 = -6/12
-x = -1/2
x = 1/2

D= - 2.4x + 5 = 7.8x - 3
D= -2.4x - 7.8x = -3 - 5
D= -10.2x = - 8
D= -10.2x/10.2 = -8/10.2
-x = -8/10.2
x = 8/10.2

2014-01-19T18:01:11+01:00
5x +3 = 8x +17
5x -8x = -3 +17
-3x = +14
x = 14/3

-3x -13 = 8x -5
-3x -8x = +13 -5
-11x = +8
x = 8/11

5x-5 = 17x -11
5x -17x = 5 -11
-12x = -6
x = -6/12

-2,4x +5 = 7,8 x -3
-2,4x -7,8x = -5 -3
-10,2x = -8
x = -8/10,2